Holy words, worldly deeds: The role of Pope Francis in Violence Against Women - Astghik Mavisakalyan; Panagiotis Sotirakopoulos; Tobden Tobden (Global Labor Organization (GLO), 2025)
This study examines the influence of religious leaders on social attitudes by analysing Pope Francis' impact on beliefs about the justification of violence against women (VAW). Using a content analysis of his speeches, we document sustained engagement with topics related to women's rights. Exploiting variation in speech timing, religious affiliation, and proximity to the Vatican, we find that greater exposure to the Pope's statements is associated with lower acceptance of VAW. The effect appears to operate through heightened salience of religious values, reinforcing moral norms, and immediate increases in online search activity and media coverage of VAW-related topics. These findings highlight the power of religious authority figures to shape social attitudes and public discourse on gender-based violence.
Keywords: D83; D91; I31; J10; J16; Z12; 330; Religion; Leaders; Pope Francis; Violence Against Women; Intimate Partner Violence